Effect of Intrathecal Bupivacaine Dose on the Success of External Cephalic Version for Breech Presentation: A Prospective, Randomized, Blinded Clinical Trial. Issue 3 (September 2018) - Chalifoux, L.A.; Bauchat, J.R.; Higgins, N.; Toledo, P.; Peralta, F.M.; Farrer, J.; Gerber, S.E.; McCarthy, R.J.; Sullivan, J.T.
Abstract : ( Anesthesiology 2017;127:625–632) Increased rate of cesarean delivery without measurable improvements in maternal or neonatal outcomes is a major public health problem. Breech presentation is a major contributor to the incidence of cesarean delivery and can be prevented by external cephalic version (ECV). Neuraxial blockade for ECV improves maternal satisfaction and procedural success and decreases maternal pain. Meta-analysis of randomized controlled trials suggests that administering higher doses of local anesthetic (LA) for neuraxial block leads to increased ECV success, although the protocol for providing neuraxial blockade for this procedure has not yet been standardized.